IMPROVEMENT OF THE CRIMINAL LAW AND LIABILITY STANDARD FOR NON-EXECUTION OF COURT DOCUMENTS (World Conference on Social Sciences, Law and Public Policy, 2026)
This thesis examines the issues of correct qualification of the crime of non-execution of court documents in the Republic of Uzbekistan and improvement of the norm establishing liability for it. The study analyzes the main problems in practice, including the separation of criminal and administrative liability, confusion between debt and enforcement obligations, as well as difficulties in determining punishment fairly and proportionally. The article also presents proposals on the separation of special and general norms, the issuance of systematic instructions to courts, and the application of Articles (232, 233) of the Criminal Code.
Keywords: Failure to execute court documents, criminal liability, qualification, Criminal Code, administrative liability, debt, judicial practice, sentencing, special norm, general norm.